Petrochronology of the migmatization event of the Xolapa Complex, Mexico, microchemistry and equilibrium growth of zircon and garnet. Issue 11 (17th August 2016) - Estrada-Carmona, Juliana; Solari, Luigi A.; Ortega-Obregón, Carlos
ABSTRACT: The number of migmatization events in the Xolapa Complex and their absolute age are controversial. U–Pb dating by laser ablation–inductively coupled plasma–mass spectrometry was performed on zircon grains from migmatites to investigate the age of different textural domains. Rare-earth element (REE) partition coefficients between zircon and garnet were compared with those established for different temperatures in order to test for equilibrium growth. Two age domains were identified. In one sample where zircon and garnet coexist, the outer zircon overgrowths yield a mean age of 54.16 ± 0.29 Ma (mean square weighted deviation (MSWD) = 3.5), whereas intermediate zones, between the core and outer overgrowths, yield an age of 122.7 ± 1.8 Ma (MSWD = 2.5). Partition coefficients were calculated for REEs between coexisting garnet (two different populations) and zircon using (1) the composition of ca. 54 Ma zircon overgrowths and garnet rims and (2) zircon intermediate zones together with garnet cores. The cores of small garnet grains (garnet A) may have grown in equilibrium with zircon domains of ca. 122 Ma. Both garnet cores and rims of the larger porphyroblasts (garnet B) seem to be in equilibrium with ca. 54 Ma zircon overgrowths. Petrographic observations suggest that crystallization of garnet A occurred during partial melting, placing equilibrium growth and therefore a first migmatitic event during the Early Cretaceous at ca. 122 Ma. This migmatitic event may be related to the collision of the Chortís Block with western Mexico. A second migmatitic event of ca. 54 Ma is suggested by equilibrium growth of large garnets (group B) and the outer zircon overgrowths. The high geothermal gradient necessary for this second migmatitic event might be related to the exhumation of the Xolapa Complex, as a result of the transpression and tectonic transport of the Chortís Block to the southeast from the end of the Mesozoic to most of the Cenozoic.